Paramagnetic Iron-Doped Hydroxyapatite Nanoparticles with Improved Metal Sorption Properties. A Bio-Organic Substrates-Mediated Synthesis - Mercado Castro, Donaldo Fabio (2014)
This paper describes the synthesis of paramegnetic iron-containing hydroxyapatite nanoparticles and their increased Cu2+ sorbent capacity when using Ca2+ complexes of soluble bio-organic substrates from urban wastes as synthesis precursors. A thorough characterization of the particles by TEM, XRD, FTIR spectroscopy, specific surface area, TGA, XPS, and DLS, indicates that loss of crystallinity, a higher specific area, an increased surface oxygen content, and formation of surface iron phases strongly enhance Cu2+ adsorption capacity of hydroxyapatite-based materials. However, the major effect of the surface and morphologycal modifications is the size diminution of the aggregates formed in aqueous solutions leading to an increased effective surface available for Cu2+ adsorption. Maximum sorption values of 550 - 850 mg Cu2+ per gram of particles suspended in an aqueous solution at pH 7 were determined; almost 10 times the maximum values observed for hydroxyapatite nanoparticles suspensions under the same conditions.